PHYSICAL TRAUMA -A LEADING CAUSE OF MEDICO LEGAL CASES AT DHQ HOSPITAL ABBOTTABAD - Hassan, Qudsia; Bashir, M. Zahid; Shah, Mian Mujahid (Journal of Ayub Medical College Abbottabad, 2010)
Background: Trauma is one of leading cause of suffering to mankind. No study has yet been done to see the incidence, pattern of injury, outcome and declaration according to Qisas and Diyat in the city of Abbottabad. The objectives of the study were to determine the frequency of age and sex with type of lesion and causative weapon after trauma in a medico-legal clinic and to find the impact on the commonest target organs in the study area. Methods: This cross-sectional study was conducted at District Headquarter Hospital, Abbottabad between 1st January 2004 and 31st December 2004. Cases presenting for medico legal examination in Medico-legal Department of DHQ Hospital Abbottabad. Patients were selected on basis of purposive sampling technique. Physical trauma group was sub-divided into firearms, sharp, blunt and road traffic accident. This group was further classified according to age, sex, area of body involved, type of weapon, seasonal prevalence, and whether injuries were declared according to Qisas and Diyat ordinance. Results: A total of 759 cases of physical trauma reported for medico-legal examination. Out of 759 cases of physical trauma, 3.4% cases of firearm weapon, 7.9% cases of sharp weapon, 16.2% of road traffic accidents, and 72.5% of blunt weapon presented in the medico-legal clinic. Male preponderance with 97% was noted. Two-third of victims were between 10 and 39 years of age. The months of May-July and October-December showed slightly elevated number of cases. The head and neck was the most commonly involved area. No case was certified according to Qisas and Diyat Ordinance. Conclusion: Physical trauma constitutes the leading cause to the mankind which makes about 91.6% of cases. Males between 10 to 39 years of age are most likely to be victims. The face and head is the most affected area. Keywords: Injury, Blunt trauma, road traffic accidents, Qisas and Diyat